Kon-Tiki: spatio-temporal maps for socio-economic sustainability. Issue 3 (5th August 2014) - Gilbert Ahamer, Professor Glenn Hardaker, Dr; Ahamer, Gilbert
<x content-type="archive" xml:space="preserve">Abstract</x> Purpose – The overall purpose of this paper is to detect spatial, temporal, sectoral, thematic and other patterns or transitions in techno-socio-economic evolution that are likely to co-determine future development and allow the steering of it. The development of a "Global Change Data Base" (GCDB) promises a graphically and geographically oriented tool for the representation of correlations for global long-term data series. Design/methodology/approach – A literature analysis supports the interpretation of such "pattern recognitions", especially the literature in the areas of economic growth, systems analysis, energy economics, social indicators and quality of life. Preconditions for economic growth are empirically analysed on a sectoral level along with prevailing structural shifts in the use of energy sources. Findings – The main outcome is a distillate of a few formative "paths of development", according to a synthesis of to-date growth theories. These lines might influence development in future decades and co-determine the degree to which sustainability targets are met. Debates and discussion procedures make use of such findings and outline modes of actions. Practical implications – Developmental university curricula such as "Global Studies", democratisation endeavours based on analyses of economic performance of (partly) democratic systems or global governance of science could profit from a consensus on global trends patterns, similar to the Intergovernmental Panel on Climate Change endeavour at the United Nations level. Social implications – Such heuristic methods could suitably mediate (in "multicultural" manner) between contradictory paradigms of global economic development that are mainly ideology-driven and hamper global society's joint action. Originality/value – In short, this is an empirical work on pattern recognition in global evolution using aggregated spatially and temporally enabled data. It refers to the historic example of Kon-Tiki which undertook a surprisingly long journey based on precise knowledge of ocean currents and wind without applying own force.